High-Velocity Clouds - van Woerden, Hugo; Wakker, Bart; Schwarz, Ulrich; de Boer, Klaas (Astrophysics and Space Science Library, 2005)
On the occasion of the retirement of Ulrich Schwarz, a symposium was held in Groningen in May of 1996, celebrating his contributions to the study of the int- stellar medium, including his work on the high-velocity clouds. The coming together of many specialists in the latter ?eld prompted the idea of compiling a book c- taining their contributions, and summarizing the status of our understanding of the high-velocity cloud phenomenon. This seemed especially worthwhile at the time, since many exciting developments were taking place. After the discovery of some H i clouds with high velocities, about 40 years ago, the subject had been dominated by 21-cm observations of H i emission. Starting in the mid-1980s much progress was being made because of the availability of new instruments, such as large ground-based optical telescopes and UV observatories in space. The connections between the work on high-velocity clouds and other studies of the properties of the (hot) interstellar medium also became clearer.